2014
DOI: 10.1128/aem.00712-14
|View full text |Cite
|
Sign up to set email alerts
|

Improved Production of a Heterologous Amylase in Saccharomyces cerevisiae by Inverse Metabolic Engineering

Abstract: cThe increasing demand for industrial enzymes and biopharmaceutical proteins relies on robust production hosts with high protein yield and productivity. Being one of the best-studied model organisms and capable of performing posttranslational modifications, the yeast Saccharomyces cerevisiae is widely used as a cell factory for recombinant protein production. However, many recombinant proteins are produced at only 1% (or less) of the theoretical capacity due to the complexity of the secretory pathway, which ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 55 publications
0
26
0
1
Order By: Relevance
“…The best clone B184 had a nearly sixfold improvement in α-amylase production. In our previous work the mutant that was selected manually, M715 (12), had only about a 1.5-fold improvement in SD-2×SCAA medium (an optimized medium for protein production) compared with the wild-type strain AAC. This shows a clear potential of high-throughput screening from large libraries for selecting cell factories with improved desired phenotype.…”
Section: Resultsmentioning
confidence: 99%
“…The best clone B184 had a nearly sixfold improvement in α-amylase production. In our previous work the mutant that was selected manually, M715 (12), had only about a 1.5-fold improvement in SD-2×SCAA medium (an optimized medium for protein production) compared with the wild-type strain AAC. This shows a clear potential of high-throughput screening from large libraries for selecting cell factories with improved desired phenotype.…”
Section: Resultsmentioning
confidence: 99%
“…To fully exploit strain engineering as a means to enhance the secretion of relevant proteins, numerous studies have focused on generating ‘supersecreting’ strains and identifying secretion enhancing genetic elements . Early studies used random mutagenesis and plate assays to identify strains with an enhanced secretion phenotype for a particular heterologous protein.…”
Section: Rational Engineering Of the Secretory Pathway For Enhanced Smentioning
confidence: 99%
“…Recent advances in high throughput DNA sequencing technologies allowed researchers to overcome the limitations of SNP identification in supersecreting strains generated by random mutagenesis . Liu et al . obtained an S. cerevisiae strain, through UV‐random mutagenesis, that was capable of producing 5‐fold more heterologous secreted amylase than the original strain.…”
Section: Rational Engineering Of the Secretory Pathway For Enhanced Smentioning
confidence: 99%
See 1 more Smart Citation
“…This result suggests that the cell-specific secreted activities of these strains are improved under oxygen-limited conditions. Recent research has demonstrated that α-amylase enzyme production from S. cerevisiae in aerobic conditions is limited by the protein folding capacity and that higher productivity can be obtained under anaerobic conditions (80). The amylase yield increased 2-fold in anaerobic cultivation compared to aerobic conditions suggesting that amylase tends to gain higher production and reduced rates of ER misfolding in these conditions.…”
Section: )mentioning
confidence: 99%